2004
DOI: 10.1073/pnas.0404504102
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of proteoglycan synthesis by glucuronosyltransferase-I gene delivery: A strategy to promote cartilage repair

Abstract: Osteoarthritis is a degenerative joint disease characterized by a progressive loss of articular cartilage components, mainly proteoglycans (PGs), leading to destruction of the tissue. We investigate a therapeutic strategy based on stimulation of PG synthesis by gene transfer of the glycosaminoglycan (GAG)-synthesizing enzyme, ␤1,3-glucuronosyltransferase-I (GlcAT-I) to promote cartilage repair. We previously reported that IL-1␤ down-regulated the expression and activity of GlcAT-I in primary rat chondrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 33 publications
(31 reference statements)
2
55
0
2
Order By: Relevance
“…In contrast, we have been unsuccessful in gene delivery to the articular cartilage (data not shown), although a recent similar study demonstrated increased CS expression in an articular cartilage explant (38). Since CS biosynthesis occurs in the Golgi apparatus (22), the addition of the enzyme to the tissue is ineffective, and overexpression in the cell is essential for this enzyme-based increase in CS levels.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, we have been unsuccessful in gene delivery to the articular cartilage (data not shown), although a recent similar study demonstrated increased CS expression in an articular cartilage explant (38). Since CS biosynthesis occurs in the Golgi apparatus (22), the addition of the enzyme to the tissue is ineffective, and overexpression in the cell is essential for this enzyme-based increase in CS levels.…”
Section: Discussionmentioning
confidence: 73%
“…However, stubs of the linkage region have not been identified in aggrecan, although such stubs are present in a parttime CS proteoglycan thrombomodulin, an integral membrane glycoprotein expressed on endothelial cell surfaces (37). Recently, GlcAT-I, which transfers a GlcUA residue to the second Gal residue in the linkage region, has been shown to increase CS biosynthesis to ϳ1.5-fold (38). Thus, an immature linkage region may be present, and the enzyme complex that includes GlcAT-I and CSGalNAcT-1 may catalyze the completion of the linkage region and CS chain initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Durrant et al showed that cartilage explants swelled and gained Ͼ20% weight in culture (25), and Racz et al revealed that hyperosmotic conditions lead to apoptotic cell death (26). During tissue culture, additional water appears to be retained in control explants EFFECT OF GAG LOSS ON CHONDROCYTE DEATH with high GAG content and a strong negative charge (27,28). Thus, the results from our first series of studies show that GAG depletion as induced by chondroitinase ABC treatment does not directly lead to chondrocyte death.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of the gene for a heat-shock protein (Hsp70) was also shown to afford protection against cellular injuries in chondrocytes (9). Alternatively, the delivery of sequences encoding for growth and enzymatic factors can potentially stimulate cartilage anabolism in vitro and in situ, such as insulinlike growth factor 1 (IGF-1) (10), fibroblast growth factor 2 (FGF-2) (11), bone morphogenetic protein 7 (BMP-7) (12), transforming growth factor ␤ (TGF␤) (13), and glucuronosyltransferase I (14). However, application of external stimuli to damaged articular cartilage has not yet proved sufficient in fully reestablishing an original cartilage surface, and little is known about the effects on human OA cartilage.…”
mentioning
confidence: 99%